Analyzing the Efficacy of Anti-Gravity Treadmill in Enhancing Gait and Balance among Patients with Spastic Cerebral Palsy - A Critical Review - Jeevarathinam, Thirumalai; Pavithra, Aravind; Vinodhkumar, Ramalingam; Kumaresan, Abathsagayam; Jagatheesan, Alagesan; Prathap, Suganthirababu (INTI International University, 2024)
Background: In the pediatric population, cerebral palsy is the most prevalent neurological condition. As the result of prenatal or perinatal events, the cause of this complex physical disability is cast over the congenital fragility. There is often a challenge in gait and balance for individuals with spastic cerebral palsy. Innovative interventions for spastic cerebral palsy such as the anti-gravity treadmill which simulates partial weight-bearing have been sparked in innovative rehabilitation technologies. This study aims to assess published studies on anti-gravity treadmill training, evaluating their strengths and weaknesses, considering study design, sample size, outcomes, and limitations. This critical review will make recommendations for future research and address the limitations identified in the current body of literature. Methods: A quantitative research critical review form is used to analyze the eleven studies with different study designs, including 6 Randomized Control Trials, 2 Experimental Study, 1 Prospective Study, 1 Systematic review and meta-analysis and 1 study where not clearly mentioned about their study design. This review includes studies obtained from Google Scholar, PubMed, Cochrane, and ResearchGate databases. Our primary focus revolves around the studies with populations of spastic cerebral palsy and outcomes associated with balance and gait. Conclusion: This critical review concludes that the anti-gravity treadmill enhances gait and balance for children with spastic cerebral palsy. There were positive outcomes despite variations in methodologies and limited studies, including improved gait patterns and enhanced balance. In spite of the necessity for standardized research, anti-gravity treadmills may be an effective way to address the motor challenges of those with spastic cerebral palsy. The long-term efficacy of this intervention needs to be confirmed and compared with alternatives through further robust studies.